The study of early strength development of foamed concrete / Nurul Izza Hussin - Hussin, Nurul Izza (Faculty of Civil Engineering, 2006)
Foamed concrete is the latest technology in construction industries in Malaysia. Normal concrete used cement, aggregate, sand and water as materials in order to produce concrete. As for the foamed concrete, it uses same materials except replace aggregate with foaming agent which consists of synthetics and protein based. Foamed concrete has low density which is approximately 400 kg/m3 – 1800 kg/m3. Although the weight is small, it is a highly workable, self-leveling, self-compacting and good thermal insulation. It gives benefit to the construction industries as an alternative method for replacing aggregate in concrete in order to prevent from using aggregates continuously that may decrease the volume of natural aggregates besides producing better quality of the concrete. The objectives of this project is to determine the early strength for foamed concrete of density 1200 kg/m3 – 1400 kg/m3 and to conduct the study on the effect to the early strength of foamed concrete added with admixtures which is Glenium C380 and Calcium Nitrate. The scope of this project is to focus on compressive strength at early age of concrete and the effect of admixtures. There are 5 different types of cement-sand ratio; 1:1, 1:2, 1:3, 2:1 and 3:1 with density between 1200 kg/m3 – 1400 kg/m3. All work was carried out at heavy laboratory by using cube mould 100 x 100 x 100 mm. All data for the compressive strength were recorded at age 1, 7 and 28 days. Based on the results, the strength of foamed concrete with 3:1 mix proportion is the highest compressive strength meanwhile 1:3 mix proportions is the lowest one. Whilst, foamed concrete added with admixtures (Glenium C380 and Calcium Nitrate) give highest values for the compressive strength compared to the normal foamed concrete. However, among these admixtures, Glenium C380 gives highest values compared to the Calcium Nitrate.